Metal Ion Homeostasis Mediated by NRAMP Transporters in Plant Cells - Focused on Increased Resistance to Iron and Cadmium Ion - Sano, Toshio; Yoshihara, Toshihiro; Handa, Koichi; Sato, Masa H.; Nagata, Toshiyuki; Hasezawa, Seiichiro (IntechOpen, 2012)
None